Local Overexpression of V1a-Vasopressin Receptor Enhances Regeneration in Tumor Necrosis Factor-Induced Muscle Atrophy. (20th May 2014) - Costa, Alessandra; Toschi, Angelica; Murfuni, Ivana; Pelosi, Laura; Sica, Gigliola; Adamo, Sergio; Scicchitano, Bianca Maria
Abstract : Skeletal muscle atrophy occurs during disuse and aging, or as a consequence of chronic diseases such as cancer and diabetes. It is characterized by progressive loss of muscle tissue due to hypotrophic changes, degeneration, and an inability of the regeneration machinery to replace damaged myofibers. Tumor necrosis factor (TNF) is a proinflammatory cytokine known to mediate muscle atrophy in many chronic diseases and to inhibit skeletal muscle regeneration. In this study, we investigated the role of Arg-vasopressin-(AVP-)dependent pathways in muscles in which atrophy was induced by local overexpression of TNF. AVP is a potent myogenesis-promoting factor and is able to enhance skeletal muscle regeneration by stimulating Ca 2+ /calmodulin-dependent kinase and calcineurin signaling. We performed morphological and molecular analyses and demonstrated that local over-expression of the AVP receptor V1a enhances regeneration of atrophic muscle. By upregulating the regeneration/differentiation markers, modulating the inflammatory response, and attenuating fibrogenesis, the stimulation of AVP-dependent pathways creates a favourable environment for efficient and sustained muscle regeneration and repair even in the presence of elevated levels of TNF. This study highlights a novel in vivo role for AVP-dependent pathways, which may represent an interesting strategy to counteract muscle decline in aging or in muscular pathologies.